Abstract SPE 2007 Filipe+Braumann - Filipe, Patrícia A. (2008)
Scientific meeting: XV Congresso Anual da Sociedade Portuguesa de Estatística, Lisboa, Portugal, Aug 19-21, 2007. Oral communication on stochastic differential equation models of individual animal growth (from birth to maturity) for the case of varying asymptotic sizes.